2016
DOI: 10.1021/acs.chemmater.6b03896
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent and Glutathione-Responsive Biodegradable Dendritic Mesoporous Organosilica Nanoparticles for Safe Protein Delivery

Abstract: The design of smart nanocarriers that could recognize and differentiate cancer cells and normal cells is of great importance in drug delivery. Here we report the first example of cancer cell-specific degradable dendritic mesoporous organosilica nanoparticles (DDMONs). A unique pore structure-dependent glutathione (GSH)responsive degradation behavior is revealed: the degradation rates of two nanoparticles with different pore sizes are similar in normal cells ("leveling effect"), while large-pore DDMONs show a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 34 publications
2
117
0
Order By: Relevance
“…B) TEM micrographs displaying the variety of morphologies and structures of MONs and PMO NPs for biomedical applications. Reproduced with permissions from American Chemical Society, Royal Society of Chemistry, Elsevier, Springer, and Wiley …”
Section: Synthesis and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…B) TEM micrographs displaying the variety of morphologies and structures of MONs and PMO NPs for biomedical applications. Reproduced with permissions from American Chemical Society, Royal Society of Chemistry, Elsevier, Springer, and Wiley …”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…Unlike silica which has an isoelectric point around 2 and 3, it was demonstrated that PMO NPs become positively charged near pH 5.5, which was harnessed for the autonomous pH‐controlled release and delivery of drugs with various PMO NPs (see the structures of D1 , E1 , F1 in Figure A). Biodegradable organosilica nanovehicles can be prepared by adding disulfide ( D2 , E2 , F2 , B6 ), tetrasulfide ( A3 , B3 , C3 , D3 , E6 ), and oxamide bridging groups ( F6 ) into the pore walls of MONs or PMO NPs. Tailored optical properties were also garnered into MONs and PMO NPs.…”
Section: Synthesis and Propertiesmentioning
confidence: 99%
“…The 13 CNMR spectrum of the DMOHS-2S (Figure 1j)shows the characteristic peaks at 4ppm, corresponding to the ethane moieties.No peaks of CTAB were observed, confirming that CTAB had been completely removed after ethanol extraction. [15] N 2 adsorption-desorption analysis show that all three samples possess large mesopores of 14.4, 16.0, 17.7 nm, respectively (Supporting Information, Figure S2a,b). Furthermore,t he three nanoparticles exhibit similar pore volumes and Brunauer-Emmett-Teller (BET) surface areas (Supporting Information, Table S1).…”
mentioning
confidence: 92%
“…[138][139][140] To an extent, the highly sensitive proteins could also maintain their bioactivity. [120] Results revealed that the DMSNs could load a mass of RNase A. [138] In this system, the cyclic adenosine monophosphase (cAMP) was first filled in the nanopore, followed by the modification of insulin with gluconic acid as a linkage.…”
Section: Silica Nanoparticlesmentioning
confidence: 99%